The Analysis of Life Experiences of High School Students in the Era of Social Media Trends: How big is the impact on the world of education? - Bautista, Ronalyn (International Journal of Education and Teaching Zone, 2024)
This study uses a descriptive phenomenology approach to explore the lived experiences of senior high school students during the era of social media trends. The sample for this research is high school students from North Palawan who actively follow social media trends and are generally aged 15-18 years. Purposive sampling was employed to choose participants, and semi-structured interviews were conducted to gather data. The interviews were documented with consent from the participants, and the researchers determined the level of data saturation. The data were thematic, and the experiences of the senior high school students were themed as follows: perceived benefits of social media use, emotional and psychological experiences of social media use, and effects of social media trends on academic performance and well-being. The study revealed that senior high school students perceive social media use as having several benefits, such as self-expression, sharing of information, and social connectedness. Social media use also has emotional and psychological effects, which can positively and negatively impact senior high school students’ well-being. Adverse effects of social media use can include cyberbullying, online harassment, and social comparison. The study also found that social media trends can significantly affect senior high school student’s academic success and general well-being. Therefore, it is essential to implement strategies that encourage responsible social media use and well-being among students to help them navigate the digital world and thrive academically and emotionally.